(3OjhGf NGdO Hf jRjOs - (3GdCehj, CHh gGTe, NGdO Hf jRjO Hf eYGhjI Hf CHj SajGf GdCehj GdbQTj, J (B90(3g` (B708(3es
(3ChdgG (B:s
(3ChdgG(B: (3jG WGdkHG HhQjWS GdMceGA (B*** (3jG efWkbG MbG HZjQ NaGA (B*** (3gh RFHb GdTQa GdPj gJahG Hg (B*** (3aj cJHge ef LedI GdCTjGAs
(3BNQgG (B:s
(3BNQgG(B: (3jG MHJgG ef UfYI de JRd (B*** (3jYQagG GdCHQGQ hGdCUajGA (B*** (3ef aGJg GdeGA hJOHjQg (B*** (3bO aGJg GdQCj jG bdJjGs
(3jSHbg McGjI NGdO eY eQjGfS GdMcje hjdjg bUGFO eNJdaI djSJ ddDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2(3, U (B300s
(3agQS ecJHI chHQjdjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdCOHs